Freedom of information : seminar papers for Queensland. - Legal and Accounting Management Seminars Pty Ltd. (Bondi Junction, N.S.W. : LAAMS Publications, 2000)
Essential update information for legal advisors, FOI officers and government departments on accessing official information and managing requests.
Keywords: Freedom of information -- Queensland -- Congresses